Peningkatan Keterampilan Menulis melalui Model Project-Based Learning di Kelas II SD Islam Plus Al-Azhar Kota Mojokerto semester ganjil Tahun Pelajaran 2019/2020 - Muhammad Ihwan (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
Project-Based Learning is one of active learning by involving students independently with the criteria that in this learning it will also increase students' thinking power towards metacognitive such as critical thinking about projects that will be worked on through problems that are found by students. Project-Based Learning is authentic, so indirectly this learning will involve learners in constructive investigations. This study aims: 1) Describe teacher activities in learning to improve writing skills through the Project-Based Learning Model in Grade II SD Islam Plus Al-Azhar, Mojokerto City, even semester of the 2019/2020 Academic Year. 2) Describe student activities in learning to improve writing skills through the Project-Based Learning Model in Grade II SD Islam Plus Al-Azhar, Mojokerto City, even semester of the 2019/2020 Academic Year. 3) Describing learning can improve writing skills through the Project-Based Learning Model in Grade II SD Islam Plus Al-Azhar, Mojokerto City, even semester of the 2019/2020 Academic Year. This research is a collaborative classroom action research. The design of problem situations, and ways of collaboration with children, are the main focus of the meetings that take place between teachers and researchers. This research was conducted at SD Islam Plus Al-Azhar, Mojokerto City, even semester of the 2019/2020 academic year. The subjects of this study were 25 students of Grade II. Action research procedures are cyclic, namely: 1) planning, 2) implementation, 3) observation, and 4) reflection, through a series of cycles. Data collection through observation (observing), artifacts and documents (testing) and non-standard tests. Instrument test items with validity test, reliability test, calibration test (level of difficulty) and distinguishing power test. The whole data analysis process is interactive through the Miles and Huberman model with the final mix method analysis. The results of the study concluded: 1) The teacher's activity increased in Pre-Action, which resulted in 62.86 percent and increased in Cycle I by 75 percent and increased in Cycle II by 87.86 percent; 2) Student activity increased in Pre-Action to get 42.86 percent and increased in Cycle I by 65 percent and increased in Cycle II by 86.43 percent; 3) The average value of the test (Classical Absorption) has increased in Pre-Action, getting 68.4 percent results and an increase in Cycle I by 72.8 percent and an increase in Cycle II by 86 percent. Classical learning completeness has increased in Pre-Action obtained a yield of 52 percent and increased in Cycle I by 80 percent and increased in Cycle II by 88 percent.